PENGENALAN KONSEP KEPEMIMPINAN SERTA PENGORGANISASIAN DAN KETERAMPILAN KELOMPOK TANI DESA RAHABITE KECAMATAN TOARI KABUPATEN KOLAKA - Ali Baim; Raodatul Jannah; Nur Santy Asminaya; Sarinah; Putu Arimbawa; Fitrianti Handayanii; La Mpia; La Ode Muhsafaat (LPPM Universitas Al Muslim, 2025)
This community service activity contained an introduction to the concept of leadership, organization, and skills of farmer groups located in Rahabite Village, Kolaka Regency with the aim of introducing the function and importance of farmer group organizations, in order to increase cooperation and productivity of the community that is part of the farmer group. The main target of this activity is the goat farming community, mothers who are members of the Family Empowerment and Welfare (PKK), and community leaders. The method of implementing the activity was in the form of counseling and discussion about the importance of leadership, organization, and skills in livestock farmer groups. The activity evaluation was carried out to determine the extent of the participants' response and understanding of the activity by comparing changes in scores in the pre-test and post-test. This activity was attended by 30 participants who were dominated by farmers. The results of the pre-test and post-test showed that this community service activity was able to increase participants' knowledge about leadership, organization, and skills of farmer groups with an average score of 80.